2022
DOI: 10.3390/machines10090760
|View full text |Cite
|
Sign up to set email alerts
|

Wear Mechanisms and Performance of PET Shredder Blade with Various Geometries and Orientations

Abstract: Shredder blade is the main component of a shredder machine used in plastic recycling. A comparative performance study was conducted on the shredder blade with different geometries and orientations to understand its wear and shredding mechanism. Identification of the loading distribution along the shredder blades was observed in different orientations. The microstructure and hardness of the worn cutting edge and as-received shredder blade were characterised by optical microscopy, scanning electron microscopy al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The shredded workpieces crumbled randomly which might wind up at the blade pair resulting an increase of the retention percentage. Comparatively, current shredder machine was able to maintain the performance after increasing the loading of the workpieces from 1.25 kg to 5.0 kg [15]. This indicated that the small‐scale single‐shaft shredder machine able to shred a higher loading of workpieces without deteriorating its shredding performance.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…The shredded workpieces crumbled randomly which might wind up at the blade pair resulting an increase of the retention percentage. Comparatively, current shredder machine was able to maintain the performance after increasing the loading of the workpieces from 1.25 kg to 5.0 kg [15]. This indicated that the small‐scale single‐shaft shredder machine able to shred a higher loading of workpieces without deteriorating its shredding performance.…”
Section: Resultsmentioning
confidence: 81%
“…A small-scale single-shaft shredder machine for polyethylene terephthalate (workpiece) was built and the experimental procedure was done with some modification based on reference [15]. The specifications of the smallscale single-shaft shredder machine were: (i) rotational speed: 47 min À 1 and (ii) throughput: 10 kg h À 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations